Replacement of water yam (Dioscorea alata L.) indigenous root endophytes and rhizosphere bacterial communities via inoculation with a synthetic bacterial community of dominant nitrogen-fixing bacteria - Liswadiratanakul, Sumetee; Yamamoto, Kosuke; Matsutani, Minenosuke; Wattanadatsaree, Vatanee; Kihara, Shunta; Shiwa, Yuh; Shiwachi, Hironobu (Frontiers in Microbiology, 2023)
Biofertilizers containing high-density plant-growth-promoting bacteria are gaining interest as a sustainable solution to environmental problems caused by eutrophication. However, owing to the limitations of current investigative techniques, the selected microorganisms are not always preferred by the host plant, preventing recruitment into the native microbiota or failing to induce plant-growth-promoting effects. To address this, five nitrogen-fixing bacteria previously isolated from water yam (Dioscorea alata L.) plants and showing dominant abundance of 1% or more in the water yam microbiota were selected for analysis of their plant-growth-promoting activities when used as a synthetic bacterial inoculant. Water yam cv. A-19 plants were inoculated twice at 10 and 12 weeks after planting under greenhouse conditions. Bacterial communities in root, rhizosphere, and bulk soil samples were characterized using high-throughput 16S rRNA amplicon sequencing. Compared with non-inoculated plants, all bacterial communities were significantly altered by inoculation, mainly at the genus level. The inoculation effects were apparently found in the root communities at 16 weeks after planting, with all inoculated genera showing dominance (in the top 35 genera) compared with the control samples. However, no significant differences in any of the growth parameters or nitrogen contents were observed between treatments. At 20 weeks after planting, the dominance of Stenotrophomonas in the inoculated roots decreased, indicating a decline in the inoculation effects. Interestingly, only the Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium clade was dominant (>1% relative abundance) across all samples, suggesting that bacteria related to this clade are essential core bacteria for water yam growth. This is the first report to show that native bacterial communities in water yam plants can be replaced by a synthetic bacterial community, with declining in the effects of Stenotrophomonas on the modified communities several weeks after inoculation.